Bioactive compounds and health benefits of edible Rumex species-A review - Prakash Mishra, Abhay; Sharifi-Rad, Mehdi; Shariati, Mohammad Ali; Mabkhot, Yahia N; Al-Showiman, Salim S; Rauf, Abdur; Salehi, Bahare; Župunski, Milan; Sharifi-Rad, Majid; Gusain, Poonam; Sharifi-Rad, Javad; Suleria, Hafiz Ansar Rasul; et al. (Cellular and Molecular Biology, 2018)
Medicinal and food plants as well as their bioactive fractions have been used by diverse human cultures since ancient times. These plants provide multiple health benefits because of the presence of a plethora of phytochemicals including phenylpropanoids, isoprenoids, alkaloids, sulphated compounds, peptides and polysaccharides that are responsible for various biological activities such as anticancer, antioxidant, antifungal, antibacterial, anti-dysenteric, anti-inflammatory, antiulcer, anti-hypertensive and anticoagulant properties. The genus Rumex includes edible and medicinal herbs belonging to buckwheat (Polygonaceae) family, consisting of about 200 species rich in phenylpropanoids and anthraquinones. Some Rumex species have exhibited health-promoting effects and have been used as traditional foods and herbal remedies, though a limited information has been documented on their specific biological properties. Therefore, this survey aimed at reviewing the Rumex species with documented biological activity, focusing on preclinical evidences on their efficacy and safety.